Analysis of the PD-1/PD-L1 axis in human autoimmune thyroid disease: Insights into pathogenesis and clues to immunotherapy associated thyroid autoimmunity. (September 2019) - Álvarez-Sierra, Daniel; Marín-Sánchez, Ana; Ruiz-Blázquez, Paloma; de Jesús Gil, Carmen; Iglesias-Felip, Carmela; González, Óscar; Casteras, Anna; Costa, Roser Ferrer; Nuciforo, Paolo; Colobran, Roger; Pujol-Borrell, Ricardo
Abstract: Autoimmune thyroid diseases (AITDs), i.e., Graves' disease (GD) and Hashimoto thyroiditis (HT), are the most prevalent organ-specific autoimmune diseases, but their pathogenesis is still incompletely understood. The PD-1/PD-L1 pathway is an important mechanism of peripheral tolerance that has not been investigated in AITDs. Here, we report the analysis of the expression of PD-1, PD-L1 and PD-L2 in PBMCs, infiltrating thyroid lymphocytes (ITLs) and in thyroid follicular cells (TFCs) in GD, HT and multinodular goiter (MNG) patients and healthy controls PBMCs (HC). By combining flow cytometry, tissue immunofluorescence and induction experiments on primary and thyroid cell line cultures, we show that: 1) while PD-1+ T cells are moderately expanded in PBMCs from GD vs HC, approximately half of T cells in the infiltrate are PD-1+ including some PD-1 hi ; 2) PD-L1, but not PD-L2, is expressed by 81% of GD glands and in 25% of non-autoimmune glands; 3) PD-L1, was expressed by TFCs in areas that also contain abundant PD-1 positive T cells but; 4) co-localization in TFCs indicated only partial overlap between the smaller areas of the PD-L1+ and the larger areas of HLA class II+ expression; 5) IFNγ is capable of inducing PD-L1 in >90% of TFCs in primary cultures and cell lines. Collectively these results indicate that the PD-1/PD-L1 axis is operative in AITD glands and may restrain the autoimmune response. Yet the discrepancy between easy induction in vitro and the limited expression in vivo (compared to HLA) suggests that PD-L1 expression in vivo is partially inhibited in GD and HT glands. In conclusions 1) the PD-1/PD-L1 pathway is activated in AITD glands but probably not to the extent to inhibit disease progression and 2) Thyroid autoimmunity arising after PD-1/PD-L1 blocking therapies in cancer patients may result from interfering PD-1/PD-L1 tolerance mechanism in thyroid with minimal (focal) thyroiditis. Finally acting on the PD-1/PD-L1 pathway could be a new approach to treat AITD and other organ-specific autoimmunity in the future. Graphical abstract: Image 1 Highlights: T lymphocytes infiltrating GD and HT thyroids express PD-1 making them amenable to inhibition by PD-1 ligands. PD-L1 expressed by TFCs in AITD glands may restrain the autoimmune response and explain the chronicity of AITD. IFNγ is probably the cytokine inducing in vivo PD-L1 expression by TFCs. PD-1/PD-L1 pathway block in cancer immunotherapy triggers AITD as it is prevented by TFC expression of PD-L1 (proposal).